Effect of a Health Promotion Model–Based Psychoeducation Program on Healthy Lifestyle Behaviors in Individuals With Schizophrenia: A Randomized Controlled Trial - Mahinur Betül Çalişkan Şahin; Melike Dişsiz (Journal of Psychosocial Nursing and Mental Health Services, 2026)
Purpose: To evaluate the effect of a program based on Pender's Health Promotion Model (HPM) and motivational interviewing on healthy lifestyle behaviors in individuals with schizophrenia. Method: A randomized controlled trial was conducted involving 60 individuals with schizophrenia and other psychotic disorders at a community mental health center. A program based on Pender's HPM and motivational interviewing was implemented over a 6-week period and follow up was conducted at 3 and 6 months. Results: After implementation of the intervention, stress levels decreased (intervention group: mean = 22.33 [ SD = 4.45], p < .01; control group: mean = 13.70 [ SD = 2.13], p = .177), and sleep levels (intervention group: mean = 10.70 [ SD = 1.3], p < .01; control group: mean = 7.97 [ SD = 2.35], p < .01) and healthy lifestyle behaviors (intervention group: mean = 137.66 [ SD = 14.11], p < .01; control group: mean = 91.60 [13.23], p = .001) increased significantly in the intervention group compared to the control group ( p < .05). Conclusion: Pender's HPM and motivational interviewing have a positive effect on the development of healthy lifestyle behaviors in individuals with schizophrenia.